DESIGN AND IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM IN OTAK-OTAK REGATA - Jhoni Hendri; Supriyanto Supriyanto (ConCEPt - Conference on Community Engagement Project, 2022)
This project aims to design a computerized accounting system as a solution for Micro, Small, and Medium Enterprises (MSMEs) that are still constrained by the process of transaction recording and accounting reporting. The object of this work practice using one of the MSMEs from Batam City named Otak-otak Regata. Otak-otak Regata’s accounting recording and reporting system are still relatively less effective and efficient. The target of this activity itself is an accounting system adapted to the business characteristics of Otak-otak Regata that simplify the process of recording and reporting accounting but generate reliable and accurate output at the same time. Work practice conducted in Otak-otak Regata was carried out for 1 (one) semester from September 2021 to December 2021. The initial stage carried out in this activity is the collection of information about business flow and problems faced by MSMEs through interviews and observations. The collected information is then compiled into master data for the system to be designed using Microsoft Access. The result show that the designed system can generate an accurate reports through transactions that the owner of the Otak-otak Regata input into the system’s form. Further researchers are recommended to be able to properly understand the characteristics of the community service practice object used from the early stages of the activity so that the output of the activity is in accordance with what is needed